Examining the gender imbalance in the National Community Health Assistant Programme in Liberia: a qualitative analysis of policy and Programme implementation. Issue 2 (7th September 2022) - Hafez, Sali; Munyati, Bob Mwiinga; Zeno, Katie; Gbozee, Catherine K Z; Jusu, Mbalu; Reeves, Mantue S; Wesseh, C Sanford; Wiah, S Olasford; AlKhaldi, Mohammed; Johnson, Kristin; Subah, Marion
Abstract: The Revised National Community Health Services Policy (2016–2021) (RNCHSP) and its programme implementation, the Liberian National Community Health Assistant Programme (NCHAP), exhibit a critical gender imbalance among the Community Health Assistants (CHAs) as only 17% are women. This study was designed to assess the gender responsiveness of the RNCHSP and its programme implementation in five counties across Liberia to identify opportunities to improve gender equity in the programme. Using qualitative methods, 16 semi-structured interviews were conducted with policymakers and 32 with CHAs, other members of the community health workforce and community members. The study found that despite the Government of Liberia's intention to prioritize women in the recruitment and selection of CHAs, the planning and implementation of the RNCHSP were not gender responsive. While the role of community structures, such as Community Health Committees, in the nomination and selection of CHAs is central to community ownership of the programme, unfavourable gender norms influenced women's nomination to become CHAs. Cultural, social and religious perceptions and practices of gender created inequitable expectations that negatively influenced the recruitment of women CHAs. In particular, the education requirement for CHAs posed a significant barrier to women's nomination and selection as CHAs, due to disparities in access to education for girls in Liberia. The inequitable gender balance of CHAs has impacted the accessibility, acceptability and affordability of community healthcare services, particularly among women. Strengthening the gender responsiveness within the RNCHSP and its programme implementation is key to fostering gender equity among the health workforce and strengthening a key pillar of the health system. Employing gender responsive policies and programme will likely increase the effectiveness of community healthcare services.